Graphene nanogaps for the directed assembly of single-nanoparticle devices. Issue 13 (24th March 2021) - Cully, John J.; Swett, Jacob L.; Willick, Kyle; Baugh, Jonathan; Mol, Jan A.
Abstract : Manipulating matter at the nanoscale has long been a central challenge in the field of nanoscience. Here, we employ graphene nanogaps as a platform for the dielectrophoretic capture of single nanoparticles to form hybrid low-dimensional devices. Abstract : Significant advances in the synthesis of low-dimensional materials with unique and tuneable electrical, optical and magnetic properties has led to an explosion of possibilities for realising hybrid nanomaterial devices with unconventional and desirable characteristics. However, the lack of ability to precisely integrate individual nanoparticles into devices at scale limits their technological application. Here, we report on a graphene nanogap based platform which employs the large electric fields generated around the point-like, atomically sharp nanogap electrodes to capture single nanoparticles from solution at predefined locations. We demonstrate how gold nanoparticles can be trapped and contacted to form single-electron transistors with a large coupling to a buried electrostatic gate. This platform offers a route to the creation of novel low-dimensional devices, nano- and optoelectronic applications, and the study of fundamental transport phenomena.